Befriending the Quran a beginner's guide for nurturing closeness to the Quran - Ayesha Syahira 1990- (Iman Publication, 2022)
In life, we always have that one friend whom we turn to in times of happy and sad, good or bad. As Muslims, can that 'friend' be our Quran? Can the Quran be the one that you turn to when you need to be uplifted, comforted and are in need of answers?